Strategi Pembelajaran Al-Qur'an di Madrasah Ibtidaiyah: Kajian Teoritis dan Praktis - Masfufah, Masfufah (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
Quran learning in Madrasah Ibtidaiyah (MI) has an important role in the formation of character and morals of the young generation. However, in practice, the learning strategies used are often less effective in improving students' understanding of the teachings of the Quran, both in terms of understanding the meaning and its application in everyday life. This problem is exacerbated by the lack of diversity in teaching methods, limited technology, and differences in the level of understanding between students. This study aims to explore the Quran learning strategies applied in MI, identify the challenges faced, and analyze the potential use of technology in improving the quality of Quran learning. The research method used is a literature study, by analyzing various relevant literature on learning theories, Al-Quran teaching methods, and the use of technology in education. This study found that the lecture and memorization methods often used in MI tend to be ineffective in building a deep understanding of the Al-Quran. Contextual and thematic approaches that connect the teachings of the Al-Quran with students' daily lives have proven to be more effective. In addition, the integration of technology such as digital Al-Quran applications and e-learning platforms can enrich students' learning experiences, although technology accessibility is a major challenge. The implications of this study indicate the importance of innovation in Al-Quran learning strategies in Madrasah Ibtidaiyah, by emphasizing a more flexible, technology-based approach that is relevant to students' needs. Teacher training is also needed to optimize the use of methods and technology in learning.